2018
DOI: 10.5539/gjhs.v11n1p81
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities Teachers' Attitudes About Professional Development to Address the Needs of Students with Gifted and Learning Disabilities (SGLD): A Qualitative Study

Abstract: Learning disabilities teachers exercise a significant influence on the educational development of students with gifted and learning disabilities (SGLD). It is therefore important to understand their attitudes towards professional development in this area to effectively implement training and educational practices to address the needs of SGLD. The authors interviewed 8 learning disabilities teachers in Yanbu city in Saudi Arabia. The interviews were analysed using content analysis. Findings from the study sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…As was found by other researchers, our teacher participants also identified strong retention as a strength of 2e students (Baldwin et al, 2015;Alsamiri and Aljohni, 2018). The Saudi elementary school teachers in our study also indicated that twice-exceptional students have high levels of curiosity and an eagerness to learn, which was a trait also identified by Lee and Ritchotte (2019).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As was found by other researchers, our teacher participants also identified strong retention as a strength of 2e students (Baldwin et al, 2015;Alsamiri and Aljohni, 2018). The Saudi elementary school teachers in our study also indicated that twice-exceptional students have high levels of curiosity and an eagerness to learn, which was a trait also identified by Lee and Ritchotte (2019).…”
Section: Discussionsupporting
confidence: 87%
“…The literature highlights the significant role of elementary school teachers in the identification and education of students with both giftedness and learning disabilities (Alsamiri and Aljohni, 2018;Firat and Bildiren, 2022). In this regard, teachers' awareness of the characteristics of students with this combination of traits facilitates early identification and intervention for these students (Firat and Bildiren, 2022).…”
Section: Importance Of Teacher Identification Of the 2ementioning
confidence: 99%
See 2 more Smart Citations